An experimental model for hypertensive crises emergencies: Long-term high-fat diet followed by acute vasoconstriction stress on spontaneously hypertensive rats. Issue 5 (March 2018) - Liu, Hong; Su, Wei-Wei; Long, Chao-Feng; Zhang, Wei-Jian; Li, Pei-Bo; Wu, Zhong; Liao, Yin-Yin; Zeng, Xuan; Chen, Tao-Bin; Zheng, Yu-Ying; Yan, Zeng-Hao; Bi, Cong; et al.
Currently, the prevention and treatment of hypertensive crises especially when it occurs with serious adverse outcomes have led to worldwide controversy. Despite of clinical possibilities of multiple agents, clinical failures still occur frequently. Therefore, early evaluations and observations of different therapies on appropriate animals should be emphasized. In the present study, an animal model for hypertensive crises emergencies was firstly established and experimentally testified. Five-month-male spontaneously hypertensive rat was consecutively fed with 60%-Kcal fat diet for four, six, and eight weeks with body weight and blood pressure monitored every two weeks, and then followed by an acute vasoconstriction stress of 5-min ice-bath treatment in the 4-h time interval of two adrenaline injections (0.8 mg/kg). Forty-four biochemical parameters were detected, covering hepatic and renal function, blood glucose and lipid levels, myocardial enzymes and energy metabolisms, blood coagulative and anti-coagulative system, oxidative stress and anti-inflammatory cytokine, blood viscosity, and RAAS system. Six tissues including heart, brain, liver, kidney, coronary arteries, and mesenteries were removed for pathological observations with hematoxylin–eosin staining. As a result, multi-organ dysfunctions in the heart, brain, liver, kidney, vascular endothelium, and blood system were testified in the modeling rats at weeks 6 and 8. In conclusion, severe consequences of this animal model were highly similar to those in hypertensive crises emergencies, which could be further utilized in the early intervention of hypertensive crises emergencies including the possible risk factors control and efficient therapies assessment. Impact statement: In the late 90s, numerous reports predicted that 1–2% of hypertensive individuals would undergo hypertensive crises (HPC) and figures reached as high as 7% when no antihypertensive therapies were administrated. Currently, clinical failures appear frequently due to the improper or excessive medication regimen instead of the illness itself. Therefore, early evaluations and observations of HPC on appropriate animal models ahead of patients should be discussed and emphasized more widely. In the present study, an appropriate animal model for HPC emergencies was firstly established, in which the consequences of long-term high-fat diet feeding followed by an acute vasoconstriction stress on the spontaneously hypertensive rats were experimentally testified. The proposed model would have a wide application prospects in early intervention of HPC emergencies including the controls of possible risk factors and assessments of efficient therapies.